Relationship between chronic demyelination of the optic nerve and short term axonal loss. Issue 3 (21st December 2011) - Klistorner, A; Garrick, R; Paine, M; Graham, S L; Arvind, H; Van Der Walt, A; Tsonis, S; Yiannikas, C
Abstract : Background: Axonal loss is a major determinant of disability in multiple sclerosis (MS). While acute inflammatory demyelination is a principal cause of axonal transection and subsequent axonal degeneration in acute disease, the nature of chronic axonal loss is less well understood. In the current study, the relationship between degree of chronic demyelination and axonal degeneration was investigated using optic neuritis (ON) as a model. Method: 25 patients with a first episode of unilateral ON, good recovery of visual function and concurrent brain or spinal cord MRI lesions were enrolled. Axonal loss was assessed using change in retinal nerve fibre layer (RNFL) thickness between 1 and 3 years after ON. Optic nerve conduction was evaluated using latency of multifocal visual evoked potentials (mfVEP). The level of mfVEP latency delay at 12 and 36 months was considered indicative of the degree of permanent demyelination. Data from 25 age and gender matched normal controls were used for comparison. Results: RNFL thickness was significantly reduced in ON eyes at 12 months compared with controls but remained unchanged in fellow eyes. Average RNFL thickness demonstrated a small but significant reduction between 12 and 36 months for both ON and fellow eyes. Change in RNFL thickness between 12 and 36 months, however, did not correlate with the degree of mfVEP latency delay. Conclusion: The results, therefore, show no association between the degree of permanent optic nerve demyelination (as measured by latency delay) and progressive axonal degeneration, at least in the early stages of the disease. The fact that fellow eyes demonstrated a similar degree of progressive axonal loss supports this suggestion.